Karakteristik Demografi, Sosial dan Ekonomi Tenaga Kerja Wanita (TKW) Kecamatan Sendang Kabupaten Tulungagung (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2018)
.Low income and job opportunity brings some women in Kecamatan Sendang to carry mobility to overseas to be TKW. Each mobility is done because characteristics demographic, social and economic of TKW. Every migrant who has worked in migration abroad has the characteristics and conditions as a whole can provide information about motivation of TKW to be a employee woment in other country. The aims of this study are describe the characteristics of demographic, social, economic of TKW. This research is descriptive research using survey method. The population in this study is the TKW in the Kecamatan Sendang who had been worked abroad and its amount about 138 respondents. The sample which is taken as many as 100 respondents by proportional random sampling. Analysis of the data that is used single-tabulation analysis and percentage to obtain the general description of each variable. This research shows that the demographic characteristics, social and economic of TKW are evenly they have an productive age in marital status, having an education at least junior high school or equivalent, type of preliminary work as housewives without personal income and family income is low that is Rp.300.000,00-<Rp.400.000,00 and family burden was 1-3 person.